Ice age - Saldanha, Carlos; Twentieth Century-Fox Film Corporation; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. 20th Century Fox Home Entertainment, 2002)
Twenty thousand years ago, at the dawn of the Ice Age, three completely mismatched creatures have been brought together by a twist of fate. Sid, a fast-talking and comical sloth, Manfred, a moody woolly mammoth, and Diego, a sinister saber-toothed tiger reluctantly team up to help return a human baby to his father. Before their incredible journey ends, this unlikely trio will confront boiling lava pits, escape treacherous ice tunnels and meet a prehistoric squirrel-rat named Scrat who is frantically trying to bury his beloved acon.
Produced by Lori Forte ; story by Michael Wilson, ; screenplay by Michael Berg and Michael J. Wilson, ; directed by Carlos Saldanha.
Voices: Ray Romano, Denis Leary, John Leguizamo, Queen Latifah, Seann William Scott, Josh Peck, Will Arnett, Jay Leno, Chris Wedge.
MPAA rating: PG; for mild language, innuendos.
VCD, full screen Dolby Digital 5.1 surround.
Keywords: Glacial epoch -- Drama; Squirrels -- Drama; Woolly mammoth -- Drama; Animated films; Children's films; Adventure films; Comedy films